2023
DOI: 10.1111/jbi.14560
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and geographical factors structure cauliflower coral's algal symbioses across the Indo‐Pacific

Abstract: Aim:The symbioses between corals and endosymbiotic dinoflagellates have been described as a flexible relationship whose dynamics could serve as a source of resilience for coral reef ecosystems. However, the factors that drive the establishment and maintenance of this co-evolutionary relationship remain unclear. We examined the environmental and geographical factors structuring dinoflagellate communities in a wide-ranging Indo-Pacific coral to begin to address this gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 183 publications
(238 reference statements)
0
3
0
Order By: Relevance
“…Our results highlight the importance of sampling across the relevant spatial scales and environments (Connolly et al., 2005 ; Karlson & Cornell, 1998 ). Most previous studies have focused on factors structuring cryptic diversity and symbiosis by sampling across large spatial scales, such as across the entire ocean basins (Glynn et al., 2023 ; Oury et al., 2023 ; Voolstra et al., 2023 ) or across several degrees of latitude (Buitrago‐López et al., 2023 ; Marzonie et al., 2024 ; Matias et al., 2023 ; Meziere et al., 2024 ). The comparison of samples across islands and reefs over such large scales could be confounded if a species is not sampled because it was rare in the particular habitat that was sampled, or if different habitats are sampled among reefs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results highlight the importance of sampling across the relevant spatial scales and environments (Connolly et al., 2005 ; Karlson & Cornell, 1998 ). Most previous studies have focused on factors structuring cryptic diversity and symbiosis by sampling across large spatial scales, such as across the entire ocean basins (Glynn et al., 2023 ; Oury et al., 2023 ; Voolstra et al., 2023 ) or across several degrees of latitude (Buitrago‐López et al., 2023 ; Marzonie et al., 2024 ; Matias et al., 2023 ; Meziere et al., 2024 ). The comparison of samples across islands and reefs over such large scales could be confounded if a species is not sampled because it was rare in the particular habitat that was sampled, or if different habitats are sampled among reefs.…”
Section: Discussionmentioning
confidence: 99%
“…Niche breadth and overlap of cryptic species could also depend on the identity of the photosynthetic microalgae from the family Symbiodiniaceae with which they form an obligate symbiosis (Buitrago‐López et al., 2023 ; Glynn et al., 2023 ; Gómez‐Corrales & Prada, 2020 ; Hoadley et al., 2021 ; Kemp et al., 2023 ; Marzonie et al., 2024 ; Palacio‐Castro et al., 2023 ; Parkinson & Baums, 2014 ; Starko et al., 2023 ; Thornhill et al., 2014 ; Turnham et al., 2021 ). Much of the coral's nutrition relies on the photosynthetic algae to convert inorganic carbon and nitrogen to nutrients through photosynthesis and absorption of nitrogen wastes.…”
Section: Introductionmentioning
confidence: 99%
“…These results should nevertheless be considered cautiously since (1) host-symbiont associations vary over time and depth (Cunning et al, 2013) and appear driven by biogeography and environmental parameters (Glynn et al, 2023), and (2) quantitative interpretation of metabarcoding results can be misleading (Lamb et al, 2019). First, Pinzón and LaJeunesse (2011) found that Pocillopora type 1 (ORF27; probably GSH09b or GSH09c TSP ) was the only type associated to the thermotolerant Durusdinium glynnii (D1; Wham et al, 2017) in the tropical eastern Pacific.…”
Section: On the (Ir)relevance Of Symbiosis Ecology To Define Speciesmentioning
confidence: 99%